Adoption of battery electric vehicles: The role of government incentives and solar PV - Davide Cerruti; Massimo Filippini; Jonas Savelsberg (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
Electrification of the private passenger transport sector is a fundamental milestone in reducing global carbon emissions. To reach this goal, several governments introduced a series of incentive programs to encourage the adoption of battery-electric vehicles (BEVs). Two of the most widespread policies to incentivize the adoption of BEVs are discounts on the annual vehicle circulation tax and purchase rebates. This paper analyzes the causal relationship between introducing these two policies and adopting battery-electric vehicles (BEVs) in Switzerland. We also examine the effect of the diffusion of rooftop solar PV on the adoption of BEVs. We find that purchase rebates for BEVs positively affect their adoption, while the discount on the circulation tax has a minor or no effect. However, the cost-effectiveness of both policies remains low because of a free-riding problem, i.e. all buyers of a BEV are entitled to the incentives, including those who would have bought a car even in their absence. The diffusion of solar PV facilitates the adoption of BEVs.
Keywords: 330